2019
DOI: 10.1136/annrheumdis-2018-215004
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ro52 autoantibodies are associated with interstitial lung disease and more severe disease in patients with juvenile myositis

Abstract: ObjectivesAnti-Ro52 autoantibodies are associated with more severe interstitial lung disease (ILD) in adult myositis patients with antiaminoacyl transfer (t)RNA synthetase autoantibodies. However, few studies have examined anti-Ro52 autoantibodies in juvenile myositis. The purpose of this study was to define the prevalence and clinical features associated with anti-Ro52 autoantibodies in a large cohort of patients with juvenile myositis.MethodsWe screened sera from 302 patients with juvenile dermatomyositis (J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
80
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 29 publications
5
80
0
2
Order By: Relevance
“…Anti-Ro52 has been known to be associated with ILD and Raynaud's phenomenon, but some reports were controversial [1]. A juvenile myositis study showed that anti-Ro52 in DM/PM was frequently detected with anti-ARS and strongly associated with ILD in each MSA subgroup [9]. In our study, we found no greater prevalence of ILD complication with anti-Ro52-positive patients in each MSA subgroup ( Supplementary Table S1).…”
supporting
confidence: 40%
“…Anti-Ro52 has been known to be associated with ILD and Raynaud's phenomenon, but some reports were controversial [1]. A juvenile myositis study showed that anti-Ro52 in DM/PM was frequently detected with anti-ARS and strongly associated with ILD in each MSA subgroup [9]. In our study, we found no greater prevalence of ILD complication with anti-Ro52-positive patients in each MSA subgroup ( Supplementary Table S1).…”
supporting
confidence: 40%
“…The results of the study by Sabbagh et al indicated that the positive rate of anti-Ro52 autoantibodies in patients with JCTM was higher than that in those with PM and DM. However, the positive rate is also highly heterogeneous among patients with different JCTM, varying from 0 (juvenile systemic sclerosis) to 29% (juvenile idiopathic arthritis) 1. Furthermore, in subgroup analyses of this study, there was a significant difference regarding the prevalence of ILD between patients with and without anti-Ro52 autoantibodies only in JDM group, but no difference in JPM or JCTM groups.…”
mentioning
confidence: 53%
“…We read with great interest the article by Sabbagh et al 1 published in the Annals of the Rheumatic Diseases . We congratulate the authors for their accuracy and the exhaustive data presented, which clearly demonstrate the importance of anti-Ro52 autoantibodies in disease monitoring, management and prognosis in patients with juvenile myositis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We presented for the first time the association between anti-Ro52 antibodies and sST2 levels in patients with IIM. Anti-Ro52 is described as the most common myositis-associated antibody in adults with myositis, what corresponds [24]. Presence of anti-Ro antibodies in PM may be associated with conductive disturbances such as atrioventricular heart blocks and bundle branch blocks [25].…”
Section: Discussionmentioning
confidence: 99%